Regulating deferred incentive pay - Florian Hoffmann; Roman Inderst; Marcus Opp (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
Our paper evaluates recent regulatory proposals mandating the deferral of bonus payments and claw-back clauses in the financial sector. We study a broadly applicable principal agent setting, in which the agent exerts effort for an immediately observable task (acquisition) and a task for which information is only gradually available over time (diligence). Optimal compensation contracts trade off the cost and benefit of delay resulting from agent impatience and the informational gain. Mandatory deferral may increase or decrease equilibrium diligence depending on the importance of the acquisition task. We provide concrete conditions on economic primitives that make mandatory deferral socially (un)desirable.
urn:nbn:de:hebis:30:3-374832
Keywords: G28; G21; D86; 330; financial regulation; compensation design; principal-agent models